ChemInform Abstract: Mutant Manufacturers. Issue 52 (24th December 2013) - Kirschning, Andreas; Eichner, Simone; Hermane, Jekatherina; Knobloch, Tobias
Abstract Review: [semisynthesis, total synthesis, mutational biosynthesis or mutasynthesis of naural product libraries for use in medicinal chemistry.